THE EFFECTIVENESS OF GROUP TUTORING SERVICES WITH VISUALIZATION TECHNIQUES TO IMPROVE ANTI-BULLYING SELF-RESILIENCE FOR LEARNERS - Abdurrajak Abdurrajak; Alfin Siregar (LP2M IAI Al-Khairat Pamekasan, 2025)
The purpose of this study was to determine the effectiveness of group guidance services with visualization techniques in increasing students' resilience against bullying. The research method used was quantitative with a nonequivalent control group design. The sample consisted of 20 students of class VIII of MTsN 2 Medan who were divided into an experimental and a control group. The researcher prepared a bullying resistance scale that was used in the research instrument. The paired sample t-test statistical test results showed a significance value of 0.000 < 0.005, indicating a statistically significant difference between the pre-test and post-test scores in the experimental class. In contrast, the significance value of the control class was 0.021 > 0.005, indicating no significant change. The independent samples t-test results also showed a significant difference between the two groups, namely a significance value of 0.000 < 0.005. Thus, group guidance services with visualization techniques are effective in increasing students' resilience against bullying.